Keto-Enol Tautomerism in Passerini and Ugi Adducts - Pablo Pertejo; Andrea Sancho-Medina; Tomás Hermosilla; Beatriz González-Saiz; Javier Gómez-Ayuso; Roberto Quesada; Daniel Moreno; Israel Carreira-Barral; María García-Valverde (Molecules, 2021)
The use of arylglyoxal as starting material in Passerini and Ugi reactions affords β-ketoamides. This has allowed to study keto-enol tautomerism in these systems and assess the way in which the presence of acyloxy or aminoacyl groups bound to the C2 position affects such tautomerism, and to investigate the reactivity of both the enol and carbonyl forms. In this work we also prove the versatility of the Passerini reaction, since depending on the conditions to which the corresponding adducts are subjected different products of synthetic interest can be obtained.